A Comprehensive Study of Kepler Phase Curves and Secondary Eclipses: Temperatures and Albedos of Confirmed Kepler Giant Planets. (4th January 2016) - Angerhausen, Daniel; DeLarme, Em; Morse, Jon A.
Abstract: We present a comprehensive study of phase curves and secondary eclipses in the Kepler data set using all data from 16 quarters that were available in 2013-2014. Our sample consists of 20 confirmed planets with R p > 4 R e, P < 10 d, V mag < 15. Here we derive their temperatures and albedos, with an eye toward constraining models for the formation and evolution of such planets. Where there was overlap our results confirm parameters derived by previous studies, whereas we present new results for Kepler 1b-8b, 12b-15b, 17b, 40b, 41b, 43b, 44b, 76b, 77b, and 412b derived in a consistent manner. We also present light-curve analyses for Kepler 91b and Kepler 74b, which both show extra dimmings at times other than from the expected primary and secondary eclipses. Corrected for thermal emission, we find most of the massive planets from our sample to be low in albedo (< 0.1) with a few having higher albedo (>0.1).